Recent Trends and Inter-District Variations in Fertility in Orissa. - Sahoo, Harihar (2011)
The paper examines the timing and nature of fertility transition in Orissa. The trends in fertility have been assessed using the data from the Census of India and Sample Registration System. The result revealed that till the mid 1980s the decline in fertility was stalled in Orissa but the process of fertility transition was reasonably consistent and the birth rate and total fertility rate started falling substantially after that. Despite the moderately high infant mortality rate and under-5 mortality rate the state has experienced reduction in fertility which is quite remarkable in such an economically backward state. The regression analysis shows that infant mortality and female literacy are the most important variables in explaining the total fertility rate.